2015
DOI: 10.5993/ajhb.39.3.12
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Text Messaging for Physical Activity Promotion in College Students: A Formative Participatory Approach

Abstract: mHealth text messaging was well received. The results support the feasibility and acceptance of such an intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 110 publications
(97 reference statements)
4
28
0
Order By: Relevance
“…The intervention delivered in this study was valued by individual participants, since the vast majority of participants found the messaging both useful in supporting behaviour change, and personally relevant. This is consistent with previous studies indicating that participants value messaging that is personally tailored [42], and personalised message content has been associated with increased intervention efficacy [37]. Following the intervention, there was evidence of improvement in behavioural and psychosocial outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…The intervention delivered in this study was valued by individual participants, since the vast majority of participants found the messaging both useful in supporting behaviour change, and personally relevant. This is consistent with previous studies indicating that participants value messaging that is personally tailored [42], and personalised message content has been associated with increased intervention efficacy [37]. Following the intervention, there was evidence of improvement in behavioural and psychosocial outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Qualitative research and existing reviews support the use of psychological theory to help identify behavioural determinants that messages can be tailored to [10,15]. This scoping review identified a number of determinants by which messages could be tailored to, namely: Stage of Change (as described in Transtheoretical Model) [10,84], social support needs [84][85][86] and self-efficacy [10,28]. The increasing potential for intervention designers to create individually tailored messages due to advancements in technology is also apparent in the evidence base [30,87].…”
Section: Message Contentmentioning
confidence: 99%
“…One example of this are the terms tailoring and targeting. Although some authors clearly distinguish between tailoring as an exclusively individual level approach and targeting as an exclusively group level approach [16], the term tailoring has also been used to describe customisation of message content at an individual level [26], and at a group level [27]. Similarly, the term targeting has been used to describe a group-level approach [28] as well as to describe individually-customised messages [29].…”
Section: Key Definitions and Position Of Messagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al [50] found that women were not driven by competitive messages but men were. Busch et al [8] personalized persuasive strategies based on gender (measured on a fine-grained scale from masculine to feminine) and found that gender is a reliable variable for personalization, with femininity being significantly related to seven of the ten strategies.…”
Section: Introductionmentioning
confidence: 99%